Perlindungan Hukum Atas Adanya Kebakaran Hutan Di Luar Izin Usaha Perkbunan Perusahaan - Emaeve Nur Berliantari; Irwan Triadi (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Forest and land fires are natural disasters that often occur in Indonesia, especially during the dry season. These fires cause enormous environmental damage, economic losses, and social problems. In fact, large forest and land fires result in devastating smoke impacts beyond state administrative boundaries (transnational disasters). The type of research that the author will use in this research is normative juridical. The use of this type of normative juridical research is because the object of study is related to legal principles and principles as well as theories and opinions of legal experts. It can be said that normative juridical research is literature research. In general, forest fires that occur in Indonesia are caused by three main factors, namely fuel conditions, weather and social and cultural conditions of the community. Fuel conditions that are prone to fire hazards are their abundance on the forest floor, relatively low water content (dry), and continuous fuel availability. Climatic factors in the form of temperature, humidity, wind and rainfall also determine fire susceptibility. High temperatures due to direct sunlight cause fuel to dry out and become flammable, high humidity (in forests with dense vegetation) reduces the chance of forest fires occurring, wind also influences the fuel drying process and the speed at which fire spreads while rainfall influences the size of the fire. water contained in the fuel.